2007
DOI: 10.1021/ja072475x
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting MgB2 Nanohelices Grown on Various Substrates

Abstract: Masses of superconducting MgB2 nanohelices and nanowires were grown on various substrates by reaction of Mg metal with diborane (B2H6). The growth occurs via a self-catalyzed vapor−liquid−solid (VLS) mechanism. It is postulated that strain in the wires due to the presence of screw dislocations is responsible for the helical morphology. The several hundred micrometer long helices have a range of diameters and pitch and are made up of wires from 50 to 200 nm in diameter. Magnetic measurements indicate that the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…The ability to construct artificial ringlike building units has implications in the rational design of complex nanostructures for precise nanofabrication. Although much progress has been made in the synthesis of nanorings by coiling of nanobelts, all these successes are based on materials with polar surfaces [16-19]. Here, we demonstrate a new mechanism of forming nanorings by coiling of nanobelts, i.e., cation-induced asymmetric strain on top and bottom surfaces of nanobelts.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The ability to construct artificial ringlike building units has implications in the rational design of complex nanostructures for precise nanofabrication. Although much progress has been made in the synthesis of nanorings by coiling of nanobelts, all these successes are based on materials with polar surfaces [16-19]. Here, we demonstrate a new mechanism of forming nanorings by coiling of nanobelts, i.e., cation-induced asymmetric strain on top and bottom surfaces of nanobelts.…”
Section: Introductionmentioning
confidence: 79%
“…For the synthesis of inorganic nanorings by coiling of nanobelts, a polar surface–driven kinetic model has ever been proposed [16-19], and geometrically, the cation- and anion-terminated surfaces are the characteristic structure of these target compounds. To minimize the electrostatic interaction energy among the polar charges, the nanobelt dominated by polar surfaces tends to fold over, resulting in the formation of single-crystalline nanorings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated that synthesis of several new geometrical configurations with controlled morphology such as nanosprings [2,3], nanorings [2,[4][5][6][7][8] and nanohelices [9,10] from 1D nanobelts/nanowires are of special interest owing to their unique periodic and elastic properties resulting in structural flexibility that provides additional opportunities for nanoengineering.…”
Section: Introductionmentioning
confidence: 99%
“…The MgB 2 materials with usable forms such as bulk, thin film, wire, and fine particle have been prepared by conventional or new methods. [1][2][3][4][5] Some groups have employed MgCl 2 and NaBH 4 as a boron source for the preparation of MgB 2 nanopowders, 6) and for preparing MgB 2 wires, the powder-in-tube (PIT) method is conventional using the resultant MgH 2 powders. 7) It is also reported that the T c of MgB 2 is increased by laser annealing.…”
mentioning
confidence: 99%